HUBUNGAN SOSIAL EKONOMI KELUARGA DENGAN STATUS GIZI PADA ANAK USIA PRA SEKOLAH 3 – 5 TAHUN DI TAMAN KANAK – KANAK GMIM BAITHANI KOHA - Bunaen, Monalisa R.H.; Wahongan, G; Onibala, Franly (JURNAL KEPERAWATAN)
Abstract: Father’s education, family income, the number of  family dependents is very related to nutritional status in pre-school children. The purpose of social studies to find out the family with nutritional status  in pre-school children age 3-5 years old in kindergarten-Koha village children. Method in use Cross Sectional with tehknik total sampling. Sampel of 30 respondents. Data collection was doneby fiiling in a questionnaire, interview, observation. Further data collected in though with the aid of SPSS programa computer for analysis with Chi Square test with significance level (α) 0,05. Results of the research data acquired in studies that dad has some lace education (20,0%) 6 and dad have lower secondary education-high 24 (80,0%), the income of low-income families  who have no 21 (70,0%) and middle-income families have a pliers-high 9 (30,0%). While the numbers of family dependents bad category there are 22 (73,3%) and a good 8 (26,7%). Conclusions in this study there was no relationship with the father’s education nutritional status with p value = 0,072. No relationship between income families with child nutritional status with the p value= 0,004, and no relationship between the number of famiy dependents with nutritional status p value= 0,001. Keywords:Education, Family income, Number of Family Obligations , Nutritional Status. Abstrak: Pendidikan ayah, pendapatan keluarga, tanggungan keluarga sangatlah berhubungan terhadap status pada anak pra sekolah. Tujuan penelitian untuk mengetahui hubungan sosial ekonomi keluarga dengan status gizi pada anak usia pra sekolah 3-5 tahun di taman kanak-kanak desa koha. Metode yang digunakan cross sectional dengan menggunakan tehknik total sampling. Sampel 30 responden. Pengumpulan data dilakukan dengan pengisian kuesioner, wawancara, observasi. Selanjutnya data yang terkumpul di olah dengan menggunakan bantuan komputer program SPSS untuk di analisa dengan uji statistic Chi square dengan tingkat kemaknaan (α) 0,05. Hasil penelitian data yang di peroleh pada penelitian bahwa ayah yang memiliki pendidikan rendah ada (20,0% ) 6 orang dan ayah yang memiliki pendidikan menengah-tinggi 24 orang (80.0%), Pendapatan keluarga yang memiliki pendapatan rendah ada 21 (70.0%) dan keluarga yang memiliki pendapatan menengah-tinggi 9 (30.0%). Sedangkan jumlah tanggungan keluarga kategori tidak baik ada 22 (73.3%)  dan yang baik 8 (26.7%). Kesimpulan dalam penelitian ini tidak ada hubungan pendidikan ayah dengan status gizi dengan p value = 0,072. Ada hubungan antara pendapatan keluarga dengan status gizi anak dengan nilai p value = 0,004 dan ada hubungan antara jumlah tanggungan keluarga dengan status gizi nilai p value = 0,001. Kata Kunci : Pendidikan, Pendapatan Keluarga, Jumlah Tanggungan Keluarga, Status Gizi